2007
DOI: 10.1111/j.1360-0443.2007.02052.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of progression to cigarette smoking on depressed mood in adolescents: evidence from the National Longitudinal Study of Adolescent Health

Abstract: These data appear to support a complex model of the relationship between depressed mood and smoking status which includes elements of both confounding and causal models. The relationship between cigarette smoking and depression may be a factor in the development of subsequent dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
89
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 35 publications
7
89
2
Order By: Relevance
“…While it may not always be feasible to avoid chronic high stress, it is possible to reduce cigarette smoking during pregnancy (Hauge et al, 2011). Prospective evaluation of depression symptoms during pregnancy and postpartum reported greater severity in women who smoke more heavily, and it is heavy smoking that is associated with greater MAO-A levels (Ludman et al, 2000;Munafo et al, 2008;Bacher et al, 2011). Investigations into mechanisms that increase MAO-A levels and activity are a relatively new direction so this list is anticipated to grow substantially over the upcoming decade.…”
Section: Discussionmentioning
confidence: 99%
“…While it may not always be feasible to avoid chronic high stress, it is possible to reduce cigarette smoking during pregnancy (Hauge et al, 2011). Prospective evaluation of depression symptoms during pregnancy and postpartum reported greater severity in women who smoke more heavily, and it is heavy smoking that is associated with greater MAO-A levels (Ludman et al, 2000;Munafo et al, 2008;Bacher et al, 2011). Investigations into mechanisms that increase MAO-A levels and activity are a relatively new direction so this list is anticipated to grow substantially over the upcoming decade.…”
Section: Discussionmentioning
confidence: 99%
“…10 Much evidence has shown that cigarette smoking and depression are highly cooccurring. [11][12][13] The high co-occurrence of cigarette smoking behavior and mental illness highlights the importance of examining the etiology and causal relationship of this co-morbidity. Researchers have hypothesized two mechanisms to explain the relationship between early smoking and later depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 The evidence for whether cigarette smoking is a precursor of later depression as detected using data from longitudinal studies remains inconclusive. 12,27 For example, using a predominantly White sample from upstate New York followed up from 14, 16, 22 to 27 years of age, Brook et al found-after controlling for sociodemographic characteristics, childhood aggression, prior mental illness, and substance use disorders-that the cumulative frequency of tobacco use during childhood, adolescence, and young adulthood (age 22) was not associated with the risk for episodes of major depressive disorder at age 27. When broken down by each time frame, however, they found that tobacco use prior to the early 20s (adolescence and earlier) predicted major depression in the late 20s, while tobacco use in the early 20s did not predict major depression in the late 20s.…”
Section: Introductionmentioning
confidence: 99%
“…First, depressive disorders may lead to cigarette use (Nezami et al, 2005;Wu & Anthony, 1999). Using data from the National Longitudinal Study of Adolescent Health, Munafò and colleagues (2008) found that among individuals who had never smoked at baseline, increases in depressive symptoms lead to smoking initiation but not to becoming regular smokers (Munafò, Hitsman, Rende, Metcalfe, & Niaura, 2008). Some have suggested that mood disorders may lead individuals to smoke due to their need to alleviate distressing symptoms they may be experiencing (Khantzian, 1997).…”
Section: Comorbidity Of Depression and Cigarettes Use: Etiological Comentioning
confidence: 99%
“…Empirical investigations in the United States have shown that higher levels of depression are observed among adolescents who are current smokers, compared to levels of depression among adolescents who have never smoked and those who are former smokers (Martini, Wagner, & Anthony, 2002), but the exact mechanisms for this association have yet to be uncovered. For example, using longitudinal data from the United States National Longitudinal Study of Adolescent Health, Steuber and Danner (2006) found that current smokers were more likely to experience depressive symptoms, even after controlling for prior level of depression (Munafò et al, 2008;Steuber & Danner, 2006). For the past two decades, a considerable amount of empirical attention has been devoted to understanding the genetic factors associated with cigarette smoking.…”
Section: Comorbidity Of Depression and Cigarettes Use: Etiological Comentioning
confidence: 99%